Green biosynthesis of bimetallic selenium–gold nanoparticles using Pluchea indica leaves and their biological applications - Aly Khalil, Ahmed Mohamed; Saied, Ebrahim; Mekky, Alsayed E.; Saleh, Ahmed M.; Al Zoubi, Omar Mahmoud; Hashem, Amr H. (Frontiers in Bioengineering and Biotechnology, 2024)
The increasing bacterial resistance and negative impacts of the present antibacterial agents have emerged the need for novel antibacterial agents and anticancer drugs. In this regard, nanotechnology could provide safer and more efficient therapeutic agents. The main methods for nanoparticle production are the chemical and physical approaches that are often costly and environmentally unsafe. In the current study, Pluchea indica leaf extract was used for the biosynthesis of bimetallic selenium-gold nanoparticles (Se-Au BNPs) for the first time.Phytochemical examinations revealed that the P. indica leaf extract includes 90.25 mg/g DW phenolics, 275.53 mg/g dry weight (DW) flavonoids, and 26.45 mg/g DW tannins. X-ray diffraction (XRD), transmission electron microscopes (TEM), Fourier-transform infrared spectroscopy (FTIR), dynamic light scattering (DLS), scanning electron microscope (SEM), and energy dispersive X-ray spectroscopy (EDX) techniques were employed to characterize Se-Au BNPs. Based on UV-Vis spectra, the absorbance of Se-Au BNPs peaked at 238 and 374 nm. In SEM imaging, Se-Au BNPs emerge as bright particles, and both Au and Se were uniformly distributed throughout the P. indica leaf extract. XRD analysis revealed that the average size of Se-Au BNPs was 45.97 nm. The Se-Au BNPs showed antibacterial properties against Escherichia coli, Pseudomonas aeruginosa, Staphylococcus aureus, and Bacillus subtilis, with minimum inhibitory concentrations (MICs) of 31.25, 15.62, 31.25, and 3.9 µg/ml, respectively. Surprisingly, the cytotoxicity assay revealed that the IC 50 toward the Wi 38 normal cell line was 116.8 µg/ml, implying that all of the MICs described above could be used safely. More importantly, Se-Au BNPs have shown higher anticancer efficacy against human breast cancer cells (MCF7), with an IC 50 of 13.77 µg/ml. In conclusion, this paper is the first to provide data on the effective utilization of P. indica leaf extract in the biosynthesis of biologically active Se-Au BNPs.